The myth of sacred prostitution in antiquity - Budin, Stephanie Lynn (Cambridge University Press, 2008)
Introduction -- The ancient Near Eastern data -- The so-called "evidence" -- Herodotos -- Mylitta and Mulissu -- In the footsteps of Herodotos : Lucian and "Jeremiah" -- Pindar fragment 122 -- Strabo, confused and misunderstood -- Klearkhos, Justinus, and Valerius Maximus -- Archaeological "evidence" from Italy -- The early Christian rhetoric -- Last myths